CD8+ T cell exhaustion in anti‐tumour immunity: The new insights for cancer immunotherapy. Issue 1 (14th November 2022) - Huang, Yijin; Jia, Anna; Wang, Yufei; Liu, Guangwei
Abstract: CD8 + T cells play a crucial role in anti‐tumour immunity, but they often undergo exhaustion, which affects the anti‐tumour activity of CD8 + T cells. The effect and mechanism of exhausted CD8 + T cells have become the focus of anti‐tumour immunity research. Recently, a large number of studies have confirmed that long‐term antigen exposure can induce exhaustion. Cytokines previously have identified their effects (such as IL‐2 and IL‐10) may play a dual role in the exhaustion process of CD8 + T cells, suggesting a new mechanism of inducing exhaustion. This review just focuses our current understanding of the biology of exhausted CD8 + T cells, including differentiation pathways, cellular characteristics and signalling pathways involved in inducing exhaustion, and summarizes how these can be applied to tumour immunotherapy. Abstract : This summarized the current understanding of the biology of exhausted CD8 + T cells, including differentiation pathways, cellular characteristics, and signaling pathways involved in inducing exhaustion, and how these can be applied to tumor immunotherapy.